Road to the Olympics: Physical fitness of medalists of the Canoe Sprint Junior European and World Championship events over the past 20 years - Bielik, V.; Lendvorsky, L.; Lengvarsky, L.; Lopata, P.; Petriska, R.; Pelikanova, J. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: In this article we aimed to find out whether there is a difference in physiological, anthropometric and power variables between medalists in junior international Championship events (MJCH) and the remaining members of the national team (NT) in flat water canoe sprint. METHODS: Sixty male junior kayakers from Slovak NT were tested annually between years 1995 and 2016. Sixteen of them won at least one medal (gold, silver or bronze) at junior international Championship. Exercise capacity assessment on treadmill running (TR) and kayak ergometer (KE), anthropometric and muscle power measurements were performed between years 1995 and 2016. RESULTS: MJCH were on average by 10% better in TR speed and KE power output at VO2max than the rest of NT (19.72±0.8 vs. 18±1.0 km/h, P<0.01, ES=1.84; 206.6±21.5 vs. 182.3±25.5 W, P<0.01, ES=0.99, respectively). Similarly mean maximal power in bench press and bench pull was higher in MJCH (522.9±72.0 vs. 464.3±69.0 W, P<0.01; ES=0.84; 629.15±63.3 vs. 571.6±58.7 W, P<0.01; ES=0.96, respectively). CONCLUSIONS: These data show that an athlete has to be on average by 10% better in physical fitness than the rest of NT to take podium position at canoe sprint junior international Championship. Prosperous juniors are further successful at senior Championship events and Olympics. We assume that high level of physical fitness in junior age is not a guarantee but a prerequisite for a successful future career.